Linalool isomerase, a membrane-anchored enzyme in the anaerobic monoterpene degradation in Thauera linaloolentis 47Lol. Issue 1 (December 2016) - Marmulla, Robert; Šafarić, Barbara; Markert, Stephanie; Schweder, Thomas; Harder, Jens
Abstract Background Thauera linaloolentis 47Lol uses the tertiary monoterpene alcohol (R, S )-linalool as sole carbon and energy source under denitrifying conditions. The conversion of linalool to geraniol had been observed in carbon-excess cultures, suggesting the presence of a 3, 1-hydroxyl-Δ1 -Δ2 -mutase (linalool isomerase) as responsible enzyme. To date, only a single enzyme catalyzing such a reaction is described: the linalool dehydratase/isomerase (Ldi) fromCastellaniella defragrans 65Phen acting only on (S )-linalool. Results The linalool isomerase activity was located in the inner membrane. It was enriched by subcellular fractionation and sucrose gradient centrifugation. MALDI-ToF MS analysis of the enriched protein identified the corresponding gene namedlis that codes for the protein in the strain with the highest similarity to the Ldi. Linalool isomerase is predicted to have four transmembrane helices at the N-terminal domain and a cytosolic domain. Enzyme activity required a reductant for activation. A specific activity of 3.42 ± 0.28 nkat mg * protein−1 and a kM value of 455 ± 124 μM were determined for the thermodynamically favored isomerization of geraniol to both linalool isomers at optimal conditions of pH 8 and 35 °C. Conclusion The linalool isomerase fromT. linaloolentis 47Lol represents a second member of the enzyme class 5.4.4.4, next to the linalool dehydratase/isomerase fromC. defragrans 65Phen. Besides considerable amino acid sequence similarity both enzymes share common characteristics with respect to substrate affinity, pH and temperature optima, but differ in the dehydratase activity and the turnover of linalool isomers.